Lymphocyte subsets, TNF? and interleukin-4 levels in treated and untreated subacute sclerosing panencephalitis patients - Anlar, B; Guven, A; Köse, G; Okur, H; Kose, O; Aydin, OF; Serdaroglu, A (Elsevier Science Bv, 2005)
Immunologic studies in relation to clinical status might help to understand the pathogenesis of subacute sclerosing panencephalitis (SSPE) and the effect of treatment. We measured lymphocyte subsets and intracellular TNF alpha and interleukin-4 levels in peripheral blood in SSPE patients. Patients had elevated percentages of CD8+ cells compared to age-matched control children. Rapidly progressive course was associated with increased CD4+ cells. Treatment with interferons and inosiplex altered the percentage of CD3+, CD4+ and CD19+ cells. TNF alpha and interleukin-4 levels had no correlation with course or treatment. The proportions of lymphocyte subsets appear to have a role in the evolution or manifestations of SSPE, if not in the pathogenesis. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: subacute sclerosing panencephalitis; lymphocyte; immunity; flow cytometry